Economic values of productive and functional traits in sheep of Bulgarian dairy synthetic population - Slavova, S.; Laleva, S. (Agricultural science and technology, 2021)
The subject of the current research was to calculate profitability and economic values of production and functional traits in sheep of Bulgarian dairy synthetic population, reared at the Agricultural Institute – Stara Zagora. The study period was 7 years (2010-2016) and the average annual number of ewes in the flock was 188. The semi-intensive production system practised involved winter indoor lambing and summer grazing on pasture. Data were processed using the Program for calculating economic weights for sheep EWSH2. Profit and profitability in the flock had negative values – (-52.70 BGN) and -19.3%. Marginal economic values of the most important traits in dairy sheep – milk production and number of lambs born per ewe were estimated to 0.707 BGN per liter and 65.40 BGN per lamb, respectively. Litter size, milk yield, conception rate of ewes and ewe lambs and productive lifetime of ewes showed the highest economic importance. A very low economic weight was calculated for the wool production due to the market prices of wool. Conception rate of female animals and productive lifetime of ewes need to be more thoroughly investigated, as they are not currently an object of selection in dairy sheep breeding. Achieving competitive and economically sustainable productive systems in sheep farming is associated with a constant desire to increase the economic value of animals.